High‐performance Sn‐based anode with robust lignin‐derived hard carbon support for sodium‐ion batteries. Issue 4 (20th March 2022) - Wang, Jie; Yin, Huanhuan; Wang, Ziqi; Gao, Jiafeng; Jiang, Qiwen; Xu, Yutong; Chen, Zui
Abstract: Tin anode has great potential for sodium‐ion batteries owing to its high theoretical capacity, but its tremendous volume expansion during the sodium (de)alloying processes leads to the structural degradation and cycling instability. Herein, we report a new design strategy by using low‐cost enzymatic hydrolysis lignin‐derived hard carbon as an ideal support for Sn particles dispersion. Sn can be uniformly anchored on the robust carbon substrate, to efficiently relieve Sn volume expansion upon cycling. In addition, conductive hard carbon support can facilitate electrons to transfer and further enhance Na + storage capacity and accelerate facile Na + diffusion in the Sn/C hybrid anodes. The resultant Sn/C hybrids as anodes deliver high‐rate performance as well as distinguished cycling stability in view of high reversible capacity of 374 mAh g −1 at 20 mA g −1 and capacity retention of 91% at 1000 mA g −1 after 1000 cycles, benefiting from high electrical conductivity, highly dispersed Sn particles and suitable pore structure. This work is expected to provide fresh insight into cost‐effective Sn‐based anodes for sodium ion batteries.